Effectiveness and safety of simeprevir-based regimens for hepatitis C in Italy: The STIly observational study. Issue 27 (July 2018) - Gaeta, Giovanni Battista; Aghemo, Alessio; Menzaghi, Barbara; D'Offizi, Gianpiero; Giorgini, Alessia; Hasson, Hamid; Brancaccio, Giuseppina; Palma, Maria; Termini, Roberta
Abstract : Abstract: The combination of the direct-acting antivirals, simeprevir (SMV) and sofosbuvir (SOF), was the first highly efficacious interferon-free combination for treating patients with hepatitis C virus (HCV), and was widely used in Italy as a result. The aim of this study was to evaluate effectiveness and safety of SMV in Italian patients with HCV genotype (GT) 1 and 4 overall, by treatment regimen [SMV/SOF and SMV/SOF+ribavirin (RBV)], cirrhosis status, and GT (GT1a, GT1b, and GT4). An observational multicenter cohort study was conducted in 46 centers across Italy. Adult HCV + GT1 or GT4 patients, naive or treatment-experienced, with or without cirrhosis, who underwent treatment with a SMV-containing regimen from May to September 2015 were included. The primary endpoint was sustained virologic response (SVR), defined as undetectable serum HCV RNA levels 12 weeks after treatment end (SVR12). The secondary endpoints included duration of treatment, safety and tolerability of each treatment regimen, and SVR by treatment and according to response to previous treatment and fibrosis stage. The association between SVR and a subset of the most clinically relevant variables was investigated by a multivariate logistic regression analysis. A total of 349 HCV-positive patients treated with an SMV-based regimen were enrolled, of whom 342 received SMV/SOF ± RBV and were included in this analysis. Most patients (59.4%) were treatment-experienced and had cirrhosis (78.1%). In the group receiving SMV/SOF + RBV, most (63.1%) were treatment-experienced and 82.9% had cirrhosis. Three patients were lost to follow-up; 330 patients receiving SMV/SOF ± RBV (96.5%) were treated for 12 weeks. Overall, SVR12 was achieved by 324 patients [94.2%, 95% confidence interval (95% CI) 92–97]. When stratified by treatment and clinical and virologic characteristics, SVR12 was achieved by 77 of 79 [97.5% (95% CI 94.0–100.0)] and 247 of 263 [93.9% (95% CI 91.0–96.8)] patients receiving SMV/SOF and SMV/SOF + RBV, respectively; 132 of 139 (95.0%) naive versus 192/203 (94.6%) treatment-experienced patients; 250 of 267 (93.6%) cirrhotic and 56 of 62 (90.3%) HIV coinfected patients. SMV-based regimens were generally well tolerated. Adverse events leading to treatment discontinuations were not observed. A high proportion of patients treated with SMV/SOF-based regimens achieved SVR12 in this study. A high SVR12 rate was also achieved in patients with cirrhosis, treatment experience, and HUV coinfected patients. Abstract : Supplemental Digital Content is available in the text